Generalized seizures and transient contralateral hemiparesis following retrobulbar anesthesia: a case report - Dettoraki, Maria (BMC Anesthesiol, 2015)
BACKGROUND: Retrobulbar block is a local anesthetic technique widely used for intraocular surgery. Although retrobulbar anesthesia is considered to be relatively safe, a number of serious adverse events have been reported. To our knowledge, immediate onset of generalized seizures with contralateral hemiparesis after retrobulbar anesthesia has not been reported. CASE PRESENTATION: A 62-year-old Caucasian healthy male with a right eye retinal detachment was admitted for pars plana vitrectomy. During retrobulbar anesthesia with ropivacaine and before needle withdrawal, the patient developed twitching of the face which rapidly progressed to generalized tonic-clonic seizures. Arterial oxygen saturation decreased to 75 %. Chin lift was performed and 100 % oxygen was administrated via face mask, which increased saturation to 99 %. Midazolam 2 mg was administrated intravenously to control seizures. After cessation of seizures, left-sided hemiparesis was evident. Brain computed tomography and electroencephalogram were normal 3 h later. The patient underwent pars plana vitrectomy under general anesthesia 4 days later. CONCLUSION: Serious complications of local anesthesia for ophthalmic surgery are uncommon. We present a case in which generalized tonic-clonic seizures developed during retrobulbar anesthesia, followed by transient contralateral hemiparesis. The early onset of seizures indicated intra-arterial injection of the anesthetic. Our case suggested the need for close monitoring during the performance of retrobulbar anesthesia and the presence of well-trained personnel for early recognition and immediate management of the complications.